2004
DOI: 10.2193/0091-7648(2004)032[0739:wdfpim]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

White-tailed deer forage production in managed and unmanaged pine stands and summer food plots in Mississippi

Abstract: Nutritional habitat quality in unmanaged southeastern forests often is limited because a dense midstory and litter layer impede growth of high‐quality, shade‐intolerant forage species. Management actions often are designed to improve the quantity of natural forages and to supplement natural forages with agronomic plantings. We evaluated the use of a selective herbicide, prescribed fire, and fertilizer to improve forage production for white‐tailed deer (Odocoileus virginianus) in naturally regenerated, mature l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
40
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 6 publications
6
40
2
Order By: Relevance
“…The non-grazed crops produced on average 2230 to 5810 kg ha 1 biomass during the growing season (marrow stem kale, second-year clover mix and early-sown rape seed within exclosures). This is in the upper range of what has been shown in earlier studies where biomass produced in food plots varied between 545 and 5860 kg ha 1 over a season (Keegan et al 1989, Hehman and Fulbright 1997, Edwards et al 2004; all in southeastern Table 3 for model details.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…The non-grazed crops produced on average 2230 to 5810 kg ha 1 biomass during the growing season (marrow stem kale, second-year clover mix and early-sown rape seed within exclosures). This is in the upper range of what has been shown in earlier studies where biomass produced in food plots varied between 545 and 5860 kg ha 1 over a season (Keegan et al 1989, Hehman and Fulbright 1997, Edwards et al 2004; all in southeastern Table 3 for model details.…”
Section: Discussionsupporting
confidence: 54%
“…Furthermore, the biomass produced per unit area in our study also seems to be larger than what has been reported through other measures used for forage improvement in forest-dominated landscapes, such as burning and fertilization (leaf biomass 435 kg ha 1 ; Edwards et al 2004 in southeastern USA), ungulate-adapted slash treatment at final felling of forest stands (271 kg ha 1 winter forage, Edenius et al 2014 in Sweden), felling of seed trees (1200 kg ha 1 winter forage, Månsson et al 2010 in south-central Sweden) and establishment of willow plantations for bioenergy purposes (128-1222 kg ha 1 summer forage, Bergström and Guillet 2002 in south-central Sweden). The biomass is also larger than the amounts of forage generally available in young Scots pine dominated forests in Scandinavia (200-2000 kg ha 1 moose winter forage, Kalén and Bergquist 2004).…”
Section: Discussioncontrasting
confidence: 54%
“…they did not result in the production of additional goods such as timber or conventional crop yield. Our results show that fencing of the fields during the growing season may be a measure to substantially increase the biomass available at the end of the growing season, as also has been suggested elsewhere (Edwards et al 2004). For all target crops except second-year clover mix, there was a significant difference in plant biomass between unfenced quadrats and exclosures.…”
Section: Discussionsupporting
confidence: 80%
“…The non-grazed crops produced on average 2230 to 5810 kg ha 1 biomass during the growing season (marrow stem kale, second-year clover mix and early-sown rape seed within exclosures). This is in the upper range of what has been shown in earlier studies where biomass produced in food plots varied between 545 and 5860 kg ha 1 over a season (Keegan et al 1989, Hehman and Fulbright 1997, Edwards et al 2004; all in southeastern Figure 3. Relationship between browsing pressure in forest and distance from the food plots.…”
Section: Discussionsupporting
confidence: 60%
“…stands of the southeastern United States (Brockway and Outcalt, 2000;Edwards et al, 2004;McInnis et al, 2004). Fire is a natural process whereas selective herbicides, specifically those containing imazapyr, offer an alternative unimpeded by smoke management issues or limited burning degree days (Brennan et al, 1998;Wigley et al, 2002).…”
Section: Introductionmentioning
confidence: 99%